Measuring the Degree of Market Power in the Export Demand for Nigerian Cocoa: An Analysis of Dutch Market - Nwachukwu, Nwachukwu; ., J. C. Nwaru; . C. Paveliuc–Olariu (Journal of Social and Development Sciences, 2011)
The study examined the degree of market power in the export demand for Nigerian Cocoa with focus on the Dutch Market. The study covered the periods of 1961–2007 and data comprised published national aggregates on specific trade and macroeconomic variables from reputable sources. Two Stage Least Squares (2 SLS) approach was used in the estimation after instrumenting for simultaneity and establishing stationarity alongside cointegration relationship. Findings, on the demand side, showed that the demand for cocoa increases as income of Netherlands (importing country) increases. Total production of the non– participating countries traced out a positive relationship with demand for cocoa by the importing country while the coefficient of price of Coffee (substitute crop) possessed a negative sign. On the supply relation side, the demand for the export crop has a negative sign, indicating decreasing marginal output with respect to cost while the proxy for ocean freight rate with its negative sign, imply increasing export cost. The result further showed that there is relative competitiveness in the Dutch market on the strength of a market power coefficient -0.712 with a Lerner index of 0.122. Based on the findings, the study calls for government intervention in the agricultural export subsector with the aim to revitalize the country’s agricultural export capacity and enhance her market power via increased market shares. These interventions could be in the form of input/production subsidies, targeted export promotion programs, farm settlement, expanded export processing zones to mention but a few.